Production of austempered ductile iron gears for transmission cases - Sagin, A; Topuz, A (CARL HANSER VERLAG, 2005)
The investigations presented in this contribution were targeted to replace a gear group made up of SAE 8620 steel in army jeeps with microstructural controlled austempered ductile iron, in order to reduce the manufacturing steps. Furthermore, the vibrations were also expected to decrease, due to the application of austempered ductile iron. The fatigue resistance of unalloyed and Ni alloyed austempered ductile iron have been investigated to see if some improvement as compared to steels with cementite could be achieved. The effect of the austenization heat treatment on the fatigue resistance was studied in metallographic investigations and it turned out that the alloying elements Cu, Ni and Mo have a beneficial effect. For economical reasons, the gears were fabricated of nodular iron containing 3.98 % C, 1.89 % Si, 0.269 % Mn and 0.028 % P. Considering the fatigue resistance, a Ni alloyed material with 3.66 % C, about 1.81 % Si, 0.134 % Mn, 0.031 % P and 1.51 % Ni was chosen. The roundness of the graphites was about 93-100% and 80-85%. The gears were at first produced by austenization at 900 degrees C for 3 hours and then by austempering at 235 degrees C for 2.5 hours. The fatigue tests were performed at the maximum stresses to be expected.
Keywords: Materials Science